Repurposing Tranexamic Acid as an Anticancer Agent - Law, Mary E.; Davis, Bradley J.; Ghilardi, Amanda F.; Yaaghubi, Elham; Dulloo, Zaafir M.; Wang, Mengxiong; Guryanova, Olga A.; Heldermon, Coy D.; Jahn, Stephan C.; Castellano, Ronald K.; Law, Brian K. (Frontiers in Pharmacology, 2022)
Tranexamic Acid (TA) is a clinically used antifibrinolytic agent that acts as a Lys mimetic to block binding of Plasminogen with Plasminogen activators, preventing conversion of Plasminogen to its proteolytically activated form, Plasmin. Previous studies suggested that TA may exhibit anticancer activity by blockade of extracellular Plasmin formation. Plasmin-mediated cleavage of the CDCP1 protein may increase its oncogenic functions through several downstream pathways. Results presented herein demonstrate that TA blocks Plasmin-mediated excision of the extracellular domain of the oncoprotein CDCP1. In vitro studies indicate that TA reduces the viability of a broad array of human and murine cancer cell lines, and breast tumor growth studies demonstrate that TA reduces cancer growth in vivo. Based on the ability of TA to mimic Lys and Arg, we hypothesized that TA may perturb multiple processes that involve Lys/Arg-rich protein sequences, and that TA may alter intracellular signaling pathways in addition to blocking extracellular Plasmin production. Indeed, TA-mediated suppression of tumor cell viability is associated with multiple biochemical actions, including inhibition of protein synthesis, reduced activating phosphorylation of STAT3 and S6K1, decreased expression of the MYC oncoprotein, and suppression of Lys acetylation. Further, TA inhibited uptake of Lys and Arg by cancer cells. These findings suggest that TA or TA analogs may serve as lead compounds and inspire the production of new classes of anticancer agents that function by mimicking Lys and Arg.